Teknologi Rancang Bangun Generator Pelindung Lutut Berbasis Biomekanik Untuk Pembangkit Energi Listrik Portable Guna Mendukung Operasional Militer di Lapangan - Sugiarta, Andik; Kasiyanto, Kasiyanto; Widiatmoko, Dekki; Syafaat, Mokhammad; Achmad, Afif; Asif, Iqra (Jurnal Bumigora Information Technology (BITe), 2023)
Background: In the 5.0 era which depends on electrical energy, innovation is needed to overcome the limitations of batteries in electronic devices. An innovative device has been created that uses knee joint movement to produce renewable energy.Objective: Knee movements are converted into electrical energy through a special gearbox that rotates a generator, converting the energy to a power bank as a storage medium.Methods: This study used an experimental method.Result: This research produces 5.6 Watts of power, providing an eective solution for charging batteries in mobility conditions.Conclusion: By utilizing knee joint movements and biomechanical analysis, this tool can utilize dierences in force, angle and speed of movement to produce the required electricity.